Thailand Renal Replacement Therapy Registry 2023 Annual Data Report: Dialysis Center Providers in Thailand - Satirapoj, Bancha; Tantiyavarong, Pichaya; Chuasuwan, Anan; Lumpaopong, Adisorn; Limbutara, Kavee; Kiattilunthorn, Kraiwiporn; Thammavaranucupt, Kanin; Lumlertgul, Nuttha; Thimachai, Paramat; Rianthavorn, Pornpimol; Pichitporn, Watthikorn; Chotmongkol, Wijittra; et al. (Journal of the Nephrology Society of Thailand, 2025)
End-stage kidney disease (ESKD) has emerged as a significant public health issue in Thailand, with the number of patients requiring renal replacement therapy steadily increasing over the past decade. This trend reflects a broader regional and global rise in the prevalence of chronic kidney disease and ESKD, driven by factors such as improved survival rates, demographic changes, and increased access to RRT. In response, Thailand has implemented an updated hemodialysis policy under the Universal Coverage Scheme to offer more patient-centered care. This study analyzes data from the Thailand Renal Replacement Therapy (TRT) Registry, exploring the growth of hemodialysis and peritoneal dialysis centers, the expansion of dialysis machine availability, and the rise in specialized healthcare professionals. The insights derived from this analysis are essential in understanding current challenges and shaping future healthcare strategies to meet the growing demand for dialysis services in Thailand.